2014
DOI: 10.1038/srep06625
|View full text |Cite
|
Sign up to set email alerts
|

High expression of MAGE-A9 correlates with unfavorable survival in hepatocellular carcinoma

Abstract: Melanoma-associated antigens (MAGE)-A9 has been reported to play important roles in the development of human cancers. However, the association between MAGE-A9 expression and the clinicopathological characteristics of hepatocellular carcinoma (HCC) is not well understood. The study was to detect the expression of MAGE-A9 in human HCC and investigate the association between its expression and the clinicopathological characteristics of HCC. Reverse transcription-polymerase chain reaction (RT-PCR), one-step quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 25 publications
4
35
0
Order By: Relevance
“…Increased MAGE-A9 expression was associated with a poor prognosis in patients with ESCC. The results of the present study were consistent with previous studies carried out in hepatocellular carcinoma and non-small cell lung cancer (7,11). Additionally, the Kaplan-Meier estimator analysis demonstrated that patients with ESCC with increased MAGE-A9 expression exhibited a markedly unfavorable outcome.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Increased MAGE-A9 expression was associated with a poor prognosis in patients with ESCC. The results of the present study were consistent with previous studies carried out in hepatocellular carcinoma and non-small cell lung cancer (7,11). Additionally, the Kaplan-Meier estimator analysis demonstrated that patients with ESCC with increased MAGE-A9 expression exhibited a markedly unfavorable outcome.…”
Section: Discussionsupporting
confidence: 94%
“…The biological functions of MAGE genes remain unknown, therefore MAGE-A may be identified as a target for cancer immunotherapy. MAGE-A9 has been studied in a number of types of cancer, including hepatocellular carcinoma, breast cancer, renal carcinoma, non-small cell lung cancer and laryngeal squamous cell carcinoma (1114). MAGE-A9 has been associated with tumor recurrence and progression in bladder cancer (15).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that MAGE-A9 expression in laryngeal, hepatocellular and renal cell carcinoma, as well as in breast, ovarian, lung and colorectal cancer, is a negative prognostic marker (20)(21)(22)(23)(24)(25)(26). Based on our patient cohort, we can confirm a significant correlation (P= 0.0468) between high MAGE-A9 expression levels and lower overall patient survival.…”
Section: Discussionsupporting
confidence: 74%
“…Han et al showed that there is a significant correlation between high MAGE-A9 expression levels and a low overall survival in laryngeal squamous cell carcinoma patients (20). Similar findings were reported for hepatocellular and renal cell carcinoma as well as breast, ovarian, lung and colorectal cancer (21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 60%
“…All 100 HCC samples of TMA were entered into the survival analyses. Clinical staging was classified according to the 2002 American Joint Committee on Cancer/International Union Against Cancer TNM staging system [24]. All enrolled patients signed written informed consent and all experimental procedures were implemented following the approved protocols of Qiqhar Medical University.…”
Section: Methodsmentioning
confidence: 99%